Effect of oral antacids on disposition of intravenous enoxacin. - Nix, D E (1993)
The effect of an intensive aluminum-magnesium hydroxide antacid regimen (Maalox TC) on the disposition of intravenous enoxacin was studied in six male and six female volunteers. A single 400-mg dose of enoxacin was administered intravenously over 30 min on two occasions separated by a 1-week washout period. Thirty milliliters of Maalox TC was administered at -8, -2.5, -0.5, 1.5, 3.5, 5.5, 7.5, 9.5, 11.5, 13.5, and 15.5 h relative to the start of one enoxacin infusion. The enoxacin dose in which antacid was coadministered was randomly selected. Fourteen plasma samples were collected over 24 h, and urine was collected in two divided intervals over 48 h. Enoxacin concentrations in plasma and urine samples were determined by high-performance liquid chromatographic assays. The intensive antacid regimen did not change the total clearance (P = 0.058) or steady-state volume of distribution (P = 0.516) for enoxacin. However, the nonrenal clearance and half-life were significantly altered (P < 0.05). The mean nonrenal clearance increased from 13.27 +/- 3.33 to 15.68 +/- 2.35 liters/h (18.2%) following the antacid regimen. This effect of antacid is unlikely to be of clinical significance. Enoxacin may be administered intravenously, but not orally, without regard to antacid treatment.